Pelatihan Pembuatan E-Commerce dan Promosi Melalui Tokopedia pada UMKM Siengkong Tapiok Bogor - Suminten Suminten; Saridawati Saridawati; Bisri Bisri; Mohammad Aris (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
This community service is in collaboration with MSME partner Siengkong TapiOk Bogor. This MSME is a food business that carries an urban and sustainability theme that focuses on local Indonesian food. This business is local Indonesian food with unique and modern flavors. For this reason, Siengkong TapiOk was made a partner in this PM so that partners can become facilitators in guiding local residents to be more productive and creative to meet the economic stability of the people of Bogor. Based on the results of the situation analysis, we discussed material that could at least help overcome the existing problems. The PM theme is "Training on E-Commerce Creation and Promotion through Tokopedia Marketplace Media for MSMEs in Siengkong Tapiok Bogor". The method is a lecture containing a tutorial on how to make sales through the Tokopedia marketplace which is carried out offline in front of the participants. The target achievement of this community service activity, apart from increasing the skills of the members of the Siengkong TapiOk Bogor MSMEs, is also in the form of publications in the form of press releases and journals.